A metaheuristic for the multimodal network flow problem with product quality preservation and empty repositioning. (December 2017) - SteadieSeifi, M.; Dellaert, N.P.; Nuijten, W.; Van Woensel, T.
Highlights: We study the long-haul transportation of perishable products around Europe. We extend the fixed-charge multicommodity capacitated network flow problem. We include product quality preservation and empty unit allocation and repositioning. We propose an Adaptive Large Neighborhood Search metaheuristic. We provide a detailed computational analysis on its properties and results. Abstract: We study a transportation planning problem with multiple transportation modes, perishable products, and management of Reusable Transport Items (RTIs). This problem is inspired by the European horticultural chain. We present a Mixed Integer Programming (MIP) optimization model which is an extension of the Fixed-charge Capacitated Multicommodity Network Flow Problem (FCMNFP). The MIP integrates dynamic allocation, flow, and repositioning of the RTIs in order to find the trade-off between product freshness requirements, and operational circumstances and costs. We furthermore propose an Adaptive Large Neighborhood Search (ALNS) algorithm with new neighborhoods, and intensification and diversification strategies. We then provide detailed computational analysis on its properties, compare its results with a state-of-the-art MIP solver, and provide practical insights.